Strategi Manajemen Komunikasi Public Relation Untuk Meningkatkan Pelayanan Prima Di Kantor Kementerian Agama Kabupaten Lombok Barat - Jelantik, Sayu Kadek; Dasih, I Gusti Ayu Ratna Pramesti (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This study aims to examine the public relations (PR) communication management strategy in improving excellent service at the Office of the Ministry of Religious Affairs of West Lombok Regency. The background of this study is based on the importance of effective communication between government institutions and the community in creating quality public services. The approach used in this study is qualitative with descriptive methods. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation studies of internal office parties and community users of the service. The results of the study indicate that the PR communication strategy implemented includes planning targeted communication messages, utilizing information media such as social media and bulletin boards, and interpersonal approaches through direct services. This strategy has been proven to be able to increase public understanding of service procedures, build public trust, and strengthen the positive image of the institution. However, the study also found several obstacles such as limited human resources trained in the field of communication and the suboptimal periodic communication evaluation system. This study concludes that PR communication management that is designed systematically and contextually plays an important role in supporting excellent service. Strengthening communication capacity, using appropriate media, and involving the community in the communication process are the keys to creating effective, efficient, and humanistic public services. The implications of this study are expected to be a reference in developing PR strategies in other government agencies.